Effect Of Training On Employee Performance With Competence And Commitment As Intervening - Pramono, Abdul Chatim; Prahiawan, Wawan (APTISI Transactions on Management (ATM), 2022)
The higher the level of competition in the steel manufacturing sectors, it is necessary for the company's efforts to survive by carrying out internal strategies in the form of improving employee performance. Training is found to be one of the factors that can affect employee performance. The purpose of this study is to examine the effect of training on employee performance with competence and commitment as intervening variables. The novelty in this research is that no previous research has been found that discusses the effect of training on employee performance with the competence and commitment as intervening employees of the Chemical Recovery Plant (CRP) Coke Oven factory at a steel industry company in in Cilegon. The population in this study were employees of Dinas CRP coke oven factory at a steel industry company in Cilegon. From a total population of 63 people with the characteristics of being organic employees and having gone through two years of service, the number of samples taken is 60 people. Structural Equation Modeling was used to test the statistical significance of the path coefficients. The research findings explain that training has a positive and significant effect on competence. Training has a positive, but not significant, effect on employee performance. Competence has a positive and significant effect on employee performance, while commitment has a positive, but not significant, effect on employee performance.